Muslim women mystics the life and work of Râbia and other women mystics in Islam - Smith, Margaret 1884-1970. (Oxford Oneworld, 2001)
This book is an authoritative account of the life and teachings of the ninth-century Muslim saint, Rabia, and represents the first complete biography of this unique individual. Discussing the place of Rabia in Islamic tradition, Dr Smith offers a survey of the female saints and mystics of the Muslim world, providing an unusual insight into women's impressive contribution to the rich heritage of Islam.
I: The life of Râbia. Râbia al-Adawiyya: her birth and early years -- Rabia's choice of celibacy -- Râabi°a's asceticism and prayer-life -- Miracles -- Râabi°a's declining years -- II: Râabi°a's teaching and writings. The Sâufâi doctrine -- Repentance, patience, gratitude -- Hope and fear -- Poverty, renunciation, unification, dependence -- Love, gnosis, the vision, union -- III: Women mystics in Islâam. The position of woman in Muslim lands -- The position attained by the woman saint -- Celibacy and the monastic life -- The communion of saints -- The cult of women saints in modern Islâam.
Previously published as Rabia [: the life & work of Rabia and other women mystics in Islam] by Oneworld, 1994.
Originally a Ph. D. thesis--University of London.
Includes bibliographical references (pages [237]-241) and index.
Keywords: Råbiah al-Adawiyah -- 801?.; Women mystics -- Biography; Muslim women saints; Women in Islam; Sufism -- Doctrines; India -- Ethnic relations